A postglacial pollen diagram from Angmagssalik, East Greenland. - Bick, H. (Meddelelser om Grønland, 1978)
A pollenanalytic study of a mire at Angmagssalik, East Greenland (65°36’N-37°39’W) has been made in connection with a vegetation research of this area by F. J. A. DANIËLS (in prep.) and J. G. DE MOLENAAR (1974, 1976). Six pollen assemblage zones have been described. In the lowermost zone of the diagram we visualise a local vegetation complex of Salix scrub and Carex bigelowii grass heaths on fluviatile or colluvial sand deposits. This was probably followed by more chionophytic vegetations (heaths and showbed with Koenigia). At ca. 6000 B.P. (radiocarbon date) peat growth started: the pollen assemblage and the lithology reveal a Carex-Eriophorum mire vegetation with a.o. Comarum palustre and Sphagnum, Drepanocladus and Calliergon spp. After a second extensive zone with willow scrub and grass heaths again a mire vegetation developed, probably in rather recent time. The diagram offers some evidence for climatic fluctuations, recognised elsewhere in the arctic. During the so called "climatic optimum" (ea. 6000-2200 B.P.) the climate of East Greenland, like that of North Greenland, was presumably more oceanic (with peat growth) than in earlier and later periods. This is in contrast to the conditions in South and West Greenland. The width of the drift ice belt along the East Greenland coast is probably a very important factor for the climate of the coastal area.